Biological computing with diffusion and excitable calcium stores - H. G. E. Hentschel; Alan Fine; C. S. Pencea (Mathematical Biosciences and Engineering, 2004)
Intracellular signaling often employs excitable stores of calciumcoupled by diﬀusion. We investigate the ability of various geometric conﬁgurations of such excitable stores to generate a complete set of logic gatesfor computation. We also describe how the mechanism of excitable calcium-induced calcium release can be used for constructing coincidence detectors forbiological signals.